Secure and Consistent Job Administration Using Encrypted Data Access Policies in Cloud Systems. (December 2021) - Nagasubramanian, Gayathri; Sakthivel, Rakesh kumar; Al-Turjman, Fadi; ,
Research highlights: In this paper, efficient fast processing Advanced Encryption Standard (AES), Secure Hashing Algorithm (SHA-3) and other session key distribution mechanisms are used. The proposed SEDAP helps to understand the cloud services and accesses in different perspectives. The results of SEDAP are compared with the other existing cloud security schemes, which shows that SEDAP has 20% more stability and ensures multilevel security in cloud job administration process. Abstract: Cloud services are provided to individuals or particular communities and groups. The data produced or communicated are expected to be more secure in the cloud environment, which requires the continuous services of Cloud Service Provider (CSP). In this article, Securely Encrypted Data Access Policies (SEDAP) are configured in the cloud platform. The proposed SEDAP helps to understand the cloud services and accesses in different perspectives such as user actions, jobs initiated from users and the batches evolved from the dependent jobs. The boundary between these perspectives is used in SEDAP for providing encrypted and authenticated job administration in cloud services. In this work, efficient fast processing Advanced Encryption Standard (AES), Secure Hashing Algorithm (SHA-3) and other session key distribution mechanisms are used. The results of SEDAP are compared with the other existing cloud security schemes, which shows that SEDAP has 20% more stability and ensures multilevel security in cloud job administration process. Graphical abstract: Jobs Arrays and Flow of Data. Image, graphical abstract